The Influence of Social Class on Racial Discrimination in the Movie The Help - Dahlia Idris; Wahyuni Wahyuni; Adi Prautomo (Prologue: Journal on Language and Literature, 2020)
This research aims to analyze the influence of social class on racial discrimination in themovie The Help. There are two objectives in this research. The first is to found the form ofsocial influence. The second the effect of racial discrimination. The theory used in thisresearch is Marxism by Karl Marx. The research uses the qualitative descriptive method inanalyzing the movie. The primary data in this research is the transcripts and scene of The Help Movie The researcher. finds the form of social class, they are proletariat and bourgeoisie. Social class differencescan affect discrimination between white and black people.